Associations between active commuting to school, sleep duration, and breakfast consumption in Ecuadorian young people (2019)
Background: Daily behaviours such as active commuting to school (ACS) could be a source of physical activity, contributing to the improvement of youth cardiovascular health, however, the relationship between ACS and other aspects of a youth's health, such as sleep duration and breakfast consumption, require further clarification. The aims of this study were therefore: 1) to analyse the prevalence of modes of commuting to school, sleep duration, and breakfast consumption by age groups and gender, and 2) to analyse the association between ACS, sleep duration recommendations, and breakfast consumption by age groups and gender. Method: This cross-sectional study included 732 school-aged students of low-middle socioeconomic status, categorised into children (10-12 yr), young adolescents (13-15 yr), and older adolescents (16-18 yr). Modes of commuting to/from school, sleep duration, and breakfast consumption were self-reported. Logistic regression models were fitted to examine the association between ACS, sleep duration and breakfast consumption, analysed according to age groups and gender. Results: The percentage of students meeting sleep duration and daily breakfast recommendations was lowest in older adolescents, and highest in children (6.3% versus 50.8% p less than 0.001, and 62.1%, versus 76.8%, p = 0.001, respectively). Young adolescents and girls who met the sleep duration recommendations were more likely to be active commuters than their counterparts (OR = 4.25; 95% CI = 1.81 to 9.92, p = 0.001 and OR = 2.89; 95%CI = 1.01 to 8.27, p = 0.04, respectively). Conclusion: Young adolescents (13-15 yr) and girls who met the sleep duration recommendations during school days displayed a positive association with ACS. There was no association between ACS and breakfast consumption for any of the age groups or gender. Children (10-12 yr) were those that best meet with the adequate sleep duration and breakfast consumption recommendations. © 2019 The Author(s).